Optical nanofiber temperature monitoring via double heterodyne detection - P. Anderson; S. Jalnapurkar; E. S. Moiseev; D. Chang; P. E. Barclay; A. Lezama; A. I. Lvovsky (AIP Advances, 2018)
Tapered optical fibers (nanofibers) whose diameters are smaller than the optical wavelength are very fragile and can be easily destroyed if excessively heated by energy dissipated from the transmitted light. We present a technique for monitoring the nanofiber temperature using two-stage heterodyne detection. The phase of the heterodyne output signal is determined by that of the transmitted optical field, which, in turn, depends on the temperature through the refractive index. From the phase data, by numerically solving the heat exchange equations, the temperature distribution along the nanofiber is determined. The technique is applied to the controlled heating of the nanofiber by a laser in order to remove rubidium atoms adsorbed on its surface that substantially degrade its transmission. Almost 90% of the nanofiber’s original transmission is recovered.